Effect of Cu(NO3)2 and Cu(CH3COO)2 Activating Additives on Combustion Characteristics of Anthracite and Its Semi-Coke; Energies; Vol. 13, iss. 22 - Larionov K. B. Kirill Borisovich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Tsibulskii (Tsibulskiy) S. A. Svyatoslav Anatolievich; Tolokolnikov A. A. Anton Andreevich; Mishakov I. V. Iljya Vladimirovich; Bauman Yu. Yury; Vedyagin A. A. Aleksey Anatolievich; Gromov A. A. Aleksandr Aleksandrovich (2020, 2020)
Title screen